Guaguasi - Bardisa, Danilo; Gutiérrez Ulla, Jorge L., 1948-; Hernández, Clara; Matacena, Orestes; Puppo, Marilyn, 1950-; Hidalgo-Gato, Raymundo; Santiago, Marco; Barral, Rolando, 1939-2002; Suárez, Ramón F.; O'Farrill, Chico, 1921-2001 (Cinemateca, 2005)
Focuses on the disintegration of a young peasant's morality once he joins the revolutionary forces of Castro's Cuba. The naive peasant was expecting adventure but before his stint in the military has ended, whether he wants to be fully aware of it or not, he is a trained killer. When he falls in love with a chorus girl in Havana, Guaguasi turns to drugs and alcohol. His decline accelerates, putting both his lover and his friends at the mercy of his slipping hold on stability.